Green Business Model Innovation: Driving Competitive Advantage Through SDG-Oriented Value Creation - Noch, Muhammad Yamin (Journal of Sustainability Industrial Engineering and Management System, 2025)
This study investigates how Green Business Model Innovation (GBMI) drives competitive advantage through SDG-oriented value creation, reflecting the growing strategic significance of sustainability-driven transformation in global business contexts. The research aims to conceptualize the mechanisms through which GBMI reshapes organizational value architecture, enhances environmental and social performance, and strengthens firms’ long-term competitive positioning. Employing a qualitative methodology grounded in an integrative literature review, the study synthesizes existing theoretical frameworks, empirical findings, and emerging insights from sustainability, innovation, and strategic management research. The method involves systematic identification, evaluation, and thematic analysis of recent peer-reviewed studies, enabling the development of a comprehensive understanding of the interconnected roles of GBMI and SDG alignment. The results reveal that GBMI produces substantial organizational benefits, including enhanced resource efficiency, reduced environmental impact, strengthened innovation capability, and improved stakeholder legitimacy. These outcomes are amplified when green innovations are aligned with specific Sustainable Development Goals, which provide strategic coherence, measurable impact pathways, and stronger institutional legitimacy. The findings further indicate that SDG-oriented value creation acts as a key mediating mechanism that translates green innovation into competitive advantage by improving brand reputation, attracting sustainability-focused investors, and enabling access to emerging green markets. Overall, the study concludes that firms integrating GBMI and SDG alignment achieve superior resilience, adaptability, and strategic differentiation, positioning sustainability as a core driver of long-term competitiveness. The research contributes theoretical insights into sustainability-oriented competitive strategy and offers managerial implications for institutionalizing GBMI within organizational structures.